ANALISIS KEMAMPUAN PESERTA DIDIK DALAM MEMECAHKAN MASALAH BERDASARKAN LANGKAH-LANGKAH POLYA PADA SOAL CERITA MATERI PECAHAN KELAS V DI SDN 3 KORLEKO SELATAN LABUHAN HAJI - Tedi Asmwandi; Arjudin; Asri Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem found is that students' ability to solve story problems on fractions is still varied and tends to be low, especially at the stage of implementing the plan and reviewing according to Polya's steps. This study aims to analyze the ability of 5th grade students of SDN 3 Korleko Selatan in solving story problems on fractions based on Polya's steps. Using a descriptive qualitative method with a case study approach. The research subjects consisted of 14 students, where data were collected through tests and interviews with 3 students representing the high, medium, and low ability categories. The results of the study showed varying abilities, high-ability students were able to carry out the four Polya stages systematically, on the contrary, medium and low-ability students experienced significant difficulties, especially at the stage of implementing the plan which was marked by calculation errors, and at the review stage where they tended not to verify the answers. The main conclusion is that students' problem-solving abilities still need to be improved, especially at the implementation and review stages. Therefore, it is recommended that teachers integrate Polya's steps in learning and use models such as Problem-Based Learning for more holistic reinforcement.